Penjaminan SHMSRS pada Hak Guna Bangunan di Atas Tanah Hak Pengelolaan oleh Orang Asing - yogawan, valerie regina (JURNAL MINUTA, 2025)
In realizing a welfare state, Indonesia’s government must manage land as part of the earth properly. As is known, land is fixed and does not increase in area meanwhile the population continues to increase. Therefore, it’s necessary to build and arrange flats. In normative juridical terms, flats can be built on HGB over HPL land. Ownership of the flat is proven by SHMSRS, furthermore SHMSRS owners are only those who are designated as holders of land rights. In accordance with UUPA, holders of HGB over HPL land consist of Indonesian citizens and Indonesian legal entities. This regulation of the UUPA is a reference for the Condominium Law and the Mortgage Rights Law. The problem is that with the promulgation of the UUCK, foreigners are regulated to have the right to own SHMSRS on HGB over HPL land, giving rise to conflicting norms between UUCK and UUPA, the Condominium Law, the Mortgage Rights Law, and the principle of nationality that all applies in Indonesia. This research is based on normative research methods as well as statutory regulations and conceptual approaches with data sources and types of primary and secondary legal materials. Through the research, it shows that these conflicting norms result in the absence of legal certainty regarding the ownership of flats in HGB over HPL land which mutatis mutandis creates legal uncertainty in SHMSRS guarantees needs to be solved by using the legal principle. Nevertheless, in fact, there is still legality in guaranteeing SHMSRS on HGB over HPL by foreigners.